WRITING THESIS IN THE FIELD OF ENGLISH EDUCATION: HOW DIFFICULT IS IT FOR INDONESIAN EFL STUDENTS? - Syayid Sandi Sukandi (ELTR Journal, 2019)
This research highlights Indonesian EFL students’ problems in writing thesis in the field of English Education at a private college in Indonesia. Respondents in this research were divided into two groups: Quantitative Research Group (QRG – 1) and Qualitative Research Group (QRG – 2). In terms of references section of the thesis, ‘writing references for different sources’ was the most difficult aspect for QRG – 1 and QRG – 2 indicated that the respondents shown ‘confusion with references format’. Findings of this research emphasize that research design influenced to which degree an individual Indonesian EFL student encountered problems in the process of writing a thesis for a bachelor’s degree in English Education.